ANALISIS PENGGUNAAN MEDIA SOSIAL MICHAT SEBAGAI ALAT TRANSAKSI SEKSUAL DI KOTA MEDAN - Fauzi, Muhammad Rizky; Rasyid, Abdul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study aims to identify the factors that influence the use of MiChat as a transaction tool in the city of Medan and explain the mechanism of the transaction system. The research method used is descriptive research, which aims to provide an explanation and validation of a phenomenon under study. This descriptive research is focused on analyzing the use of MiChat social media as a means of sexual transactions in the city of Medan. The research approach used is qualitative, which produces descriptive data in the form of written or spoken words. In this study, researchers used a qualitative approach with the aim of uncovering data described by data sources and participants, so that they can obtain quality research results naturally to obtain quality results from the research conducted.